O6-benzylguanine suppression of O6-alkylguanine-DNA alkyltransferase in anaplastic gliomas - Schold, Jr, S Clifford; Kokkinakis, Demetrius M; Chang, Susan M; Berger, Mitchel S; Hess, Kenneth R; Schiff, David; Robins, H Ian; Mehta, Minesh P; Fink, Karen L; Davis, R L; Prados, Michael D (Neuro-oncology (Charlottesville, Va.), 2004)
The purpose of the study was to determine the dose of O(6)-benzylguanine (BG) that would suppress O(6)-alkylguanine-DNA alkyltransferase (AGT) activity to undetectable levels in > 90% of anaplastic gliomas, as measured 6 h after a 1-h BG infusion. Subjects who were scheduled for surgical resection of a known or presumed anaplastic glioma received a 1-h infusion of BG. Tumor tissue was surgically removed approximately 6 h after the end of the infusion and was analyzed for AGT activity. The BG dose was escalated until at least 11 of 14 subjects had no detectable AGT activity. An additional cohort of patients received the identified effective dose of BG approximately 18 h before tumor resection in order to compare our results with an earlier study using the longer time interval. In the 79 subjects who were enrolled, there was no significant toxicity that was attributed to the BG. A dose-response relationship was determined between the BG dose and the percentage of subjects with undetectable AGT. A dose of 120 mg/m(2) suppressed AGT to less than detectable levels in 17 of 18 patients when the drug-resection interval was 6 h. With an 18-h interval, only 5 of 11 subjects had undetectable AGT at the 120-mg/m(2) dose. We conclude that a BG dose of 120 mg/m(2) given 6 h before an alkylating drug would be effective in suppressing AGT and possibly potentiating the cytotoxic effects of the drug.